Intractable complicated course of tricuspid valve infective endocarditis due to non-compliance of treatment with clinical guidelines with a decisive role of molecular biological study in etiological diagnosis: a case report - E. O. Kotova; A. Yu. Moiseeva; E. A. Domonova; O. Yu. Silveytrova; A. S. Pisaryuk; P. V. Kakhktsyan; J. I. Babukhina; Zh. D. Kobalava (Рациональная фармакотерапия в кардиологии, 2023)
A clinical observation of the treatment non-compliance consequences with clinical guidelines and principles of empirical therapy selection in a female patient with intravenous drug abuse, viral hepatitis C and HIV infection, with a history of a COVID-19 and the development of uncontrolled staphylococcal infective endocarditis (IE) of the tricuspid valve, complicated recurrence of early prosthetic IE is presented. Successful treatment was achieved only by a combination of tricuspid valve replacement and the appointment of etiotropic therapy for S. aureus (MSSA). The typical clinical scenario was not accompanied by the choice of adequate empirical antibiotic therapy, despite the high suspicion of association with MSSA, which determined the complicated course of IE. Only the polymerase chain reaction of the heart valve tissue played a key role in the etiological diagnosis. The use of valve tissue polymerase chain reaction in addition to traditional microbiological methods is a valuable diagnostic study.